Exploring The Health Issues, Nutritional Well-being, And Food Security of The Elderly Population In Bangladesh - Islam, Khaleda; Rana, Md Juwel; Ahmed, Sanzid; Sultana, Marjia; Hasan, Towhid; Jahan, Syeda Nusrat (Bioresearch Communications, 2024)
The elderly population in Bangladesh is rapidly growing, posing significant challenges to healthcare, nutrition, and social support systems. This study investigates the nutritional status, morbidity patterns, and food security among the elderly in Sirajganj and Chapainnawabganj districts. A cross-sectional study was conducted on 400 elderly individuals. Nutritional status was assessed using the Mini Nutritional Assessment (MNA) and Body Mass Index (BMI), while morbidity data were gathered from self-reports and medical records. Socio-demographic factors were analyzed for their association with comorbidities, nutritional status and food insecurity using multivariable logistic regression. The study found that 36% of the elderly were malnourished, and 45% were at risk of malnutrition. Musculoskeletal pain (81%), visual impairment (65.2%), hypertension (41%), and cardiovascular disease (24.7%) were the most prevalent health issues. Age, gender, marital status, income, education, no of children, and nutritional status were significant predictors of comorbidity, poor nutritional status and food insecurity. Participants aged 71 and above, females, widowed individuals, and those with lower incomes had higher odds of multiple comorbidities. The findings reveal a high burden of malnutrition and chronic diseases among the elderly in rural Bangladesh. Socioeconomic vulnerabilities and poor nutritional status contribute to health risks, underscoring the need for comprehensive interventions targeting food security, healthcare access, and disease management for the elderly population. Bioresearch Commu. 11(1): 1769-1779, 2025 (January)